BOOK REVIEW: ‟Biblia Sacra Vulgata”, Ediţie bilingvă, ‟Evangheliile. Faptele Apostolilor” / ‟Evangelia. Actus Apostolorum”, A. MURARU – W.TAUWINKL (eds.), vol. VII, București & Iași, Ed. Universității „Alexandru Ioan Cuza” & Ed. Humanitas, 2015, 668 p. - ȘUTEU, Ștefan (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2018)
The first bilingual edition of the Vulgate Bible (“Vulgata”) and the first modern translation of the Latin Vulgate in academic format was co-published by Humanitas Publishing House of Bucharest and “Alexandru Ioan Cuza” University Publishing House of Iassy. At two centuries and a half after the intellectual and translation-related effort of Petru Pavel Aron, bishop of Blaj, the first volume of the Romanian version edited by Associate Professor Adrian Muraru and the researcher and Associate Professor Wilhelm Tauwinkl was published, from a total of eight volumes comprised in the project launched in 2010.